Anomaly of left coronary artery - Finesa Hasye; Yerizal Karani (Majalah Kedokteran Andalas, 2018)
Anomalies of the coronary artery are uncommon, with a reported incidence of 0.3% to 1.3% in the coronary angiography studies routinely performed for suspected atherosclerotic coronary disease. There were 0.92% incidence of anomalous origination of the right coronary artery from the left sinus and the 0.15% incidence of anomalous origination of the left coronary artery from the right sinus. Most coronary artery anomalies are diagnosed by invasive angiography performed to investigate suspected atherosclerotic coronary disease. There are two important managements for patient with anomaly coronary artery. First, these coronary anomalies should result in exclusion from participation in intense competitive sports to reduce the risk of a cardiac event or sudden death. Second, and more importantly, treatment for wrong sinus coronary artery anomalies are revascularization can be either surgical or percutaneous. Surgical intervention should be considered for high-risk varieties of anomalous coronary arteries, as this is the only treatment that has been demonstrated to improve coronary blood flow and carries a low morbidity and mortality.